The Effects of Prenatal Cocaine Use on Infant Development - Richardson, Gale A. (2007)
This study examined the effect of prenatal cocaine use on infant physical, cognitive, and motor development, and temperamental characteristics, controlling for other factors that affect infant development. Women were, on average, 26.8 years old, had 12 years of education, and 46% were African American. During the first trimester, 18% were frequent users of cocaine (≥ 1 line/day). The infants were, on average, 14.6 months old at this follow-up phase. Women who used cocaine during pregnancy rated their infants as more fussy/difficult and unadaptable than did women who did not use cocaine. Cocaine use in the second trimester was associated with significantly lower motor scores on the Bayley Scales of Infant Development (BSID) [9]. There was no effect of prenatal cocaine use on BSID mental performance or on growth. These findings are consistent with other reports in the literature and with the hypothesis that prenatal cocaine exposure affects development through changes in neurotransmitter systems.